Design of UWB microstrip patch antenna with variable band notched characteristics - M. M. Hasan Mahfuz; Md. Shazzadul Islam; Islam Md. Rafiqul; Mohamed Hadi Habaebi; Nazmus Sakib (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
Recently lower frequency band 4.5−5.5 GHz is proposed by the ASEAN countries for 5G cellular application and therefore, it is essential of designing an ultra-wideband (UWB) antenna for the particular band-notched characteristics. In this article, a compact tuning fork shape ultra-wideband (UWB) patch antenna with a variable band-notched characteristic has been proposed for 5G cellular application. The UWB antenna has been achieved by using a tuning fork shape with a simple partial ground plane. A pair of ring shape slits (RSS) on the ground plane has been added to achieve the band-notched characteristic. The proposed antenna has achieved a large −10 dB bandwidth of 7.8 GHz (2.9−11 GHz) and the VSWR value is less than 2 for the entire bandwidth excepted for notched frequency bands of lower 5G bands (4.5−5.5 GHz). Moreover, the antenna has a peak radiation efficiency of more than 87% for UWB and less than 27% for the notched frequency band. The notched-band is shifted with the change in the position of RSS’s within the vertical axis and thus, the variable band-notched characteristics have been achieved. Besides, the proposed antenna is compact with the dimension of 45×34 mm2 that makes it suitable for the lower band of 5G application.